Gerakan Jender Dalam Islam: Kesetaraan Relasi Perempuan dan Laki-laki menurut al-Qur'an - Evi Muafiah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2005)
This study aims to analyze the concept of gender equality in Islam based on the perspective of the Qur'an. The method used is qualitative with a thematic interpretation approach, through a literature review of Qur'anic verses, hadiths, and classical and contemporary scholars' thoughts on the relationship between women and men. The results showed that the Qur'an emphasizes the principle of equality in rights and responsibilities between men and women, despite contextual differences in roles. The concept of gender justice in Islam is oriented towards a balance of rights and obligations without demeaning either party. This study emphasizes that the gender movement in Islam must be based on the values of the Qur'an and Islamic objectives, thus producing harmonious and fair relationships in social life.